Temporal Peaks Restoration: A New Innovation - Muhammad Ahmad (Archives of Aesthetic Plastic Surgery, 2016)
There are several methods for restoring the temporal peaks. The most important point is the variable density and angulation of the hair, which ultimately give a soft and natural look. The current technique produces zones of variable density and helps to restore naturalness.